Representaciones visuales del paisaje loretano: de la autenticidad al sentido de lugar - Castillo Guzmán, Gerardo (2025)
There is a significant visual tradition that, through painting and photography, has represented the Amazonian region of Loreto and the city of Iquitos. By discussing the concepts of landscape, authenticity, and sense of place, this article aims to analyze this tradition and new emerging forms of representation. To this end, canonical images have been analyzed and more than fifteen contemporary artists have been interviewed. It is argued that: i) this tradition is anchored in landscape painting, ii) that the authenticity of these images is achieved through their ability to mimic the landscape depicted, and iii) that artists have emerged who deconstruct previous landscapes, explicitly destabilizing hegemonic visual regimes. The article concludes with the need to shift from an emphasis on authenticity to an understanding of the embodied senses of place from which visual representations emerge.